Fixing Financial Plumbing: Tax, Leaks and Base Erosion and Profit Shifting in Europe. Issue 4 (1st October 2016) - Dover, Robert
Abstract: Aggressive tax planning by multinational enterprises (MNEs) costs EU member states between €50-70 billion and €150-190 billion per annum through base erosion and profit shifting (BEPS). This tax gap has been blamed on 'unethical' companies acting legally, but inappropriately. Action to curtail this behaviour has been made possible by the confluence of two powerful movements: a popular articulation of tax morality as it relates to MNEs and the high issue salience reached as a consequence of the financial crisis and austerity in Europe, an emerging discourse around tax morality, and the efforts of prominent whistleblowers. As a result, domestic governments have removed their 'soft' veto and facilitated supranational bodies in innovating on corporate taxation, helping to rebalance the technical and structural superiority of MNEs in the international tax system.